Converting Student Support Services to Online Delivery - David E. Brigham (Athabasca University Press, 2001)
This case study describes how Regents College (soon to be Excelsior College), an accredited, private, distance education institution with administrative offices in Albany, New York addressed the structural, management, and resource issues that came into play when converting distance education programs from print-based and telephone delivery to online delivery. The study uses a systems framework to describe and analyze the circumstances and issues surrounding the creation of six student support services: electronic advising, an electronic peer network, an online database of distance courses, an online bookstore, a virtual library, and an alumni services website.